Transformacje translatorskie w przekładzie bułgarskiej bajki magicznej Trzej bracia i złote jabłko (kod estetyczny) / Translation transformations in Polish version of the Bulgarian fairy tale Trzej bracia i złote jabłko (Three Brothers and the Golden Appl - Mleczko, Joanna (Przekłady Literatur Słowiańskich, 2009)
The article discusses translation transformations in Polish version of the Bulgarian fairy tale Trzej bracia i złote jabłko (Three Brothers and the Golden Apple). The fairy tale has been published in the collection Złota moneta za słowo. Bułgarskie bajki i legendy ludowe (Golden Coin for a Word. Bulgarian Fairy Tales and Legends — selection and introduction by Georgi Minczew, Lodz 2006).The main subject of the analysis is aesthetic code of the translation — the ways the translator has shown specific features of the oral text such as repetitions, forms and clichés. The author of the article is particulary focused on traformations on syntactic level (transformations in statements structures, changes in words order and text segmentation).The choices made by the translator prove that he wasn’t fully aware what literature genre he is translating. As the result, the translation is lacking essential for folk texts, and for fairy tale in particular, stylistic features which appear in the original.